2019
DOI: 10.3390/jcm8122111
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Psychiatric Hospitalization of Children and Adolescents in Spain between 2005 and 2015

Abstract: Eating disorders are on top of chronic conditions in children and adolescents, and the most severe cases may require hospitalization. Inpatient psychiatric treatment is one of the most expensive ones and therefore the efforts when treating eating disorders should focus on avoiding and shortening admissions, as well as preventing readmissions. Advances in of eating disorders treatment lie in an accurate knowledge of those patients requiring admission. This study examined the Conjunto Mínimo Básico de Datos—the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
2
5
1
1
Order By: Relevance
“…The greater need for admission among adolescents coming from urban areas in our sample replicates previous studies reporting similar results in different cultures (Case et al, 2007;Grupp-Phelan et al, 2009; Llanes-Alvarez et al, 2019) and might, together with higher parent education, re ect more family awareness and easier access to service but might also re ect more behavioral problems with urbanization. However, the percentage of male patients (75%) in our sample was higher than expected from the actual percentage of male children in our population (51.2%) and from previous studies in other parts of the world (Boyer et al, 2013;Case et al, 2007;Llanes-Alvarez et al, 2019). This high percentage might re ect the cultural tendency to give attention to behavioral problems more in males rather than in females.…”
Section: Resultscontrasting
confidence: 80%
“…The greater need for admission among adolescents coming from urban areas in our sample replicates previous studies reporting similar results in different cultures (Case et al, 2007;Grupp-Phelan et al, 2009; Llanes-Alvarez et al, 2019) and might, together with higher parent education, re ect more family awareness and easier access to service but might also re ect more behavioral problems with urbanization. However, the percentage of male patients (75%) in our sample was higher than expected from the actual percentage of male children in our population (51.2%) and from previous studies in other parts of the world (Boyer et al, 2013;Case et al, 2007;Llanes-Alvarez et al, 2019). This high percentage might re ect the cultural tendency to give attention to behavioral problems more in males rather than in females.…”
Section: Resultscontrasting
confidence: 80%
“…For example, in a systematic review of child mental health problems in Sub-Saharan Africa, it was observed that studies using screening questionnaires observed higher prevalence rates than studies using clinical diagnostic instruments [37]. Llanes-Alvarez et al [42] and Lawrence et al [43] who also observed male preponderance in the prevalence of mental health disorder in their studies. However, our finding is at variance with the report of Ashenafi et al [40] who found a slight female preponderance in their study.…”
Section: Discussionmentioning
confidence: 98%
“…Inpatient admission rates for children and adolescents also increased by 38.1% in Germany between 2000 and 2007 with a sharp increase of service users for depressive disorders (219.6%) and hyperkinetic disorders (111.3%; Holtmann et al, 2010). A recent study from Spain also reported an increase of individuals under 18 years old admitted to psychiatric units from 27,7 per 100,000 inhabitant in 2005 to 49.8 per 100,000 inhabitant in 2015 (Llanes-Alvarez et al, 2019). In a study carried out in a French public hospital, 2.0% of the children and adolescents cared for in the emergency department were admitted to the psychiatric emergency department (Boyer et al, 2013).…”
Section: Backg Rou N Dmentioning
confidence: 97%